2014
DOI: 10.1111/iej.12346
|View full text |Cite
|
Sign up to set email alerts
|

Does the Reciproc file remove root canal bacteria and endotoxins as effectively as multifile rotary systems?

Abstract: The reciprocating single file, Reciproc, was as effective as the multifile rotary systems for the removal of bacteria and endotoxins from root canals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 27 publications
3
44
0
11
Order By: Relevance
“…Marinho et al . () showed that Reciproc, Mtwo, ProTaper and Race (FKG Dentaire, La Chaux‐de‐Fonds, Switzerland) instruments produced highly significant reductions of the bacterial load, but no significant differences in endotoxin levels were found. However, there are no available data concerning the effect of pure reciprocating motion on bacterial reduction.…”
Section: An Overview Of Studies On Reciprocating Motionmentioning
confidence: 99%
“…Marinho et al . () showed that Reciproc, Mtwo, ProTaper and Race (FKG Dentaire, La Chaux‐de‐Fonds, Switzerland) instruments produced highly significant reductions of the bacterial load, but no significant differences in endotoxin levels were found. However, there are no available data concerning the effect of pure reciprocating motion on bacterial reduction.…”
Section: An Overview Of Studies On Reciprocating Motionmentioning
confidence: 99%
“…Even with nickel‐titanium (NiTi) rotary and reciprocating instruments, it is still not possible to overcome this problem (Marinho et al . , ).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the complex anatomy, it is impossible to fully clean the root canal system during CMP with files and irrigants alone (Gomes et al 1996. Even with nickel-titanium (NiTi) rotary and reciprocating instruments, it is still not possible to overcome this problem (Marinho et al 2014(Marinho et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…This study attempted to determine whether the LPS structure is modified via chemical treatment with commonly used substances during root canal treatment, either alone or in combination, with the goal of reducing and finally eliminating LPS toxicity. Numerous studies have focused on the ability of endodontic irrigants to remove LPS from infected root canals, together with the mechanical action of endodontic instruments and irrigant dynamics (Gomes et al 2009, Marinho et al 2015a. The present study investigated the isolated action of the chemicals, without irrigant dynamics, in direct contact with LPS to elucidate their specific effects on LPS breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…, , Marinho et al . ,b). The present study investigated the isolated action of the chemicals, without irrigant dynamics, in direct contact with LPS to elucidate their specific effects on LPS breakdown.…”
Section: Discussionmentioning
confidence: 99%